Japan, Moving Toward a More Advanced Knowledge Economy, 2 : Advanced Knowledge Creating Companies. - Shibata, Tsutomu (World Bank, 2006)
These two volumes analyze Japan from the Knowledge Economy perspective, covering a wide range of sectoral issues in development including the macro economic framework, education and skills training, the national innovation system, science and technology, information and communication technology, and infrastructure. While Volume 1 explores the four pillare of the "Knowledge for Development" framework, the second volume presents up-to-date case studies of outstanding Japanese private companies that each characterize different aspects of the Knowledge Economy. By combining economics and.